Marketing and Management: As an Example of the Field of Culture and Art - Nilufar, Maratova; Kholmuminov, Muminmirzo (Researchparks Publishing, 2023)
The article describes the current problems in organizing the activities of culture and art institutions, the issues of applying modern marketing and management concepts to the activities of organizations. Also, the issues of using innovative technologies in the organization of advertising of created works, i.e. art products, and special engagement with advertising design were raised and solutions were given.